Study of Patterns of Injuries by Road Traffic Accidents - Jakaregari Srinivas (Institute of Medico-legal Publications Pvt Ltd, 2020)
210 autopsies (176 males and 34 females) aged between 2 to 70 years ware studied. 12(6.81%) males, 8(23.5%) females total 20(9.52) were aged between 2-10 years 32 (18.1%) males. 4(11.7%) females total 36(17.1%) were aged between 11-20 years. 52(29.5%) males, 12(35.2%) female total 64(30.4%) were aged between 21-30 years. 31(17.6%) males, 3(8.82%) females total 34(16.1%) aged between 31-40 years 21(11.9%) males, 2(5.81%) females, total 23(10.9%) were aged between 41-50 years 15(8.5%) males, 3(8.82%) females, total 18(8.57%) were aged between 51-60 years 13(7.3%) males, 2(5.88%) female total 15(7.14%) aged between 61-70 years. The types of riders were, 17(8.09%) pedestrian 29(13.8%) cyclist, 103(49%) were riding two wheelers. 49(23.3%) travelling in car, 12(5.71%) were Lorry drivers / bus travelers. The types of injuries were 72(34.2%) had head injury 22(10.4%) had neck injury, 31(14.7%) had injuries to lower limb, 21(10%) abdominal injuries, 34(16.1%) had injuries to thorax, 13(6.19%) had injuries to upper limb 17(8.09%) had injuries to face. This pragmatic study will be quite useful to medico legal expert to assess the age group, region wise injury, types of riders because accident is an unexpected mishap which claims life, who are in hurry and disobey the traffic rules.